PENGARUH PENGEMBANGAN KAPASITAS SUMBER DAYA MANUSIA APARATUR PEMERINTAH DAERAH TERHADAP KINERJA PEGAWAI (STUDI PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KOTA KENDARI) - Nurdin, Emillia; Wawo, Andi Basru; Julia, Lilis (JURNAL AKUNTANSI DAN KEUANGAN, 2018)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â  This research has a purpose to know The Effect of Capacity Development of the Regional Government Apparatus Human Resources to Officer Workâs Result on the Regional Finance Manager and Asset in Kendari. The samples in this research are the officers of regional finance and asset inspection institute as much 35 respondents with the sampling is sensus method. The analysis method used is the simple linear regretion analysis aided by the test tool of SPSS Ver.22.00.Â Â Â Â Â Â Â Â Â Â Â  The result of this research shows that the development capacity of apparatur human resources of regional government has a significant positive effect to the officer workâs result on the regional Finance Manager and Asset Institute in Kendari. Based on the comparation result know that the count value (3,720) and sig value (0,001) < from Î± (0,05). The determination coefficient value shows the R Square value amount of 29,4%, in this case shows that the free variable is good enough, while the remain as amount of 70,6% effected by the other variable not researched.Key Words : The Capacity Development of Human Resources, the Work Result of Officers